Amphiphilic and Biocompatible DNA Origami‐Based Emulsion Formation and Nanopore Release for Anti‐Melanogenesis Therapy (Small 45/2021). Issue 45 (11th November 2021) - Huang, Hao; Belwal, Tarun; Li, Li; Xu, Yanqun; Zou, Ligen; Lin, Xingyu; Luo, Zisheng
Abstract : DNA Origami‐Based Emulsion An amphiphilic triangular DNA origami successfully attaches onto the water‐in‐oil and oil‐in‐water interfaces to solely stabilize the W/O/W emulsion. The DNA origami‐based emulsion is functionalized as a material platform for a bind‐and‐release of specific cargos. More information can be found in article 2104831 by Xingyu Lin, Zisheng Luo, and co‐workers.